Combien d'accents en français? Focus sur la France, la Belgique et la Suisse - Boula de Mareüil, Philippe; Scherrer, Yves; Goldman, Jean-Philippe (My University, 2017)
Two experiments are reported, an accent identification test and a survey aiming at mapping pronunciation variants in European French. The results of the first experiment show that French varieties spoken in Quebec and Paris (supposed to represent the norm) are identified best, before the Maghrebian accent. In Europe, southern accents are rather well distinguished from northern French, Belgian and Swiss accents. In the second experiment, which focuses on the quality of mid vowels and the pronunciation of final consonants, a clear North-South divide is shown. The pronunciation of some words also distinguishes Belgian and Swiss accents. Despite a certain discrepancy between production and perception, we hypothesise that 8 accents may be considered in European French: North, East, West, South-East and South-West of France, Corsica, Belgium and Switzerland.
Keywords: perceptual dialectology; geolinguistics; diatopic variation; sociophonetics; accent identification; pronunciation variants; linguistic mapping; crowdsourcing